Commercial Law - Lee mei pheng, Ivan jeron detta (Oxford, 2011)
In short, this book presents the legal principles affecting and shaping businesses and industries in Malaysia. The authors' comprehensive experience in legal practice, banking and teaching have enabled them to provide a condensed and easy to understand coverage of business law principles and areas of interest related thereto.